2012
DOI: 10.1016/j.scr.2012.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous and intra-arterial administration of bone marrow mononuclear cells after focal cerebral ischemia: Is there a difference in biodistribution and efficacy?

Abstract: Intravascular delivery of cells has been increasingly used in stroke models and clinical trials. We compared the biodistribution and therapeutic effects of bone marrow mononuclear cells (BMMCs) delivered by intra-arterial (IA) or intravenous (IV) injection after cortical ischemia. For the biodistribution analyses, BMMCs were labeled with (99m)Technetium ((99m)Tc). At 2 h, gamma-well counting of the brain and of the other organs evaluated did not show differences between the non-ischemic and ischemic groups or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 30 publications
0
52
0
Order By: Relevance
“…In a prior report, we found no differences in the biodistribuition of MNCs that were derived from bone marrow before versus after stroke when the MNCs were examined at 24 hrs after injection but we did not examine earlier time points 16 . In another relevant study, Vasconcelos-dos-Santos et al labeled donor-derived bone marrow MNCs with 99m Tc 7 and found no difference in labeling in the brain or other organs from early time points to 24 hrs after delivery and similarly found that both IV and IA led to similar effects on stroke recovery 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prior report, we found no differences in the biodistribuition of MNCs that were derived from bone marrow before versus after stroke when the MNCs were examined at 24 hrs after injection but we did not examine earlier time points 16 . In another relevant study, Vasconcelos-dos-Santos et al labeled donor-derived bone marrow MNCs with 99m Tc 7 and found no difference in labeling in the brain or other organs from early time points to 24 hrs after delivery and similarly found that both IV and IA led to similar effects on stroke recovery 7 .…”
Section: Discussionmentioning
confidence: 99%
“…IV administration is least invasive but given pulmonary sequestration may not deliver cells to the same extent to the brain 2 . Few studies have directly compared delivery routes and the results are conflicting 6, 7 . In this study, we performed a direct comparison of the effects of IV versus IA delivery of autologous MNCs in the rodent stroke model and assessed for potential differences in biodistribution, behavioral outcome, and selected mechanistic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Kamiya and colleagues were able to show decreased lesion size and motor function when compared to control animals with intra-arterial but not with intravenous administration (Kamiya et al, 2008). Alternatively, other studies comparing intra-arterial with intravenous administration of BM-MNC have shown no difference in behavioral/functional or structural outcomes in several animal models (Vasconcelos-dos-Santos et al, 2012;Yang et al, 2013). In addition, intravenous administration was found to cause potentially beneficial attenuation of cytokines with greater decreases in IL-1β and increases in IL-10 when compared to intraarterial administration (Yang et al, 2013).…”
Section: Does Route Matter?mentioning
confidence: 98%
“…Importantly, the latter adversity can be surpassed with slower injection rates [143] , a generally overlooked variable. It was reported that carotid artery delivery favors cell migration to the brain if compared to tail vein delivery route [146] . However, no differences in this aspect were seen when comparing carotid artery and jugular vein stem cell injections [147] .…”
Section: Preclinical Studies: An Heterogeneous Approach For An Heteromentioning
confidence: 99%